Pengaruh Kompentensi Tehadap Kinerja Karyawan Pada PT. PLN-T Unit Tolitoli - Ayu Wandira M. Morad; M. Sina, Angella; Joko Prathomo (Jurnal Actual Organization Of Economic, 2023)
This research aims to determine and analyze the influence of competency on employee performance at PT. PLN-T Tolitoli Unit. This research uses a quantitative research design. The type and source of data is primary data. Data collection methods were obtained through observation, documentation and questionnaires. The data analysis methods used are simple linear regression analysis, determination test, and t test. The sampling method is saturated sampling. The results of this research prove that competence has a positive and significant effect on employee performance at PT. PLN-T Tolitoli Unit. This can be seen from the SPSS 26 output results with regression analysis of variables which show a positive correlation coefficient (R) (0.562) and the t-count value of the competency variable (7.404) > t table is appropriate at the 5% significance level (1.682). This is means the higher the competence of employees at PT. PLN Tolitol Unit, the higher the employee performance will be